2002
DOI: 10.1034/j.1399-6576.2002.460514.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring arterial blood pressure during whole body hyperthermia

Abstract: The mean arterial pressure and not the systolic and/or diastolic pressure should guide hemodynamic management during WBH. The sphygmomanometric technique is not recommended for use during hyperthermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In some cases, local hyperthermia at a temperature of 42 • to 43 • C for 30 to 60 min is used to treat brain tumor tissue in animals (Sminia et al, 1994). Such heat doses lead to hemorrhages and necrosis in the surrounding brain tissue with limited changes in whole-body physiology (Kerner et al, 2002). Local or regional heating of the brain is often associated with edema formation and cell injury (van der Zee, 1987;Sminia et al, 1994).…”
Section: 1421mentioning
confidence: 99%
“…In some cases, local hyperthermia at a temperature of 42 • to 43 • C for 30 to 60 min is used to treat brain tumor tissue in animals (Sminia et al, 1994). Such heat doses lead to hemorrhages and necrosis in the surrounding brain tissue with limited changes in whole-body physiology (Kerner et al, 2002). Local or regional heating of the brain is often associated with edema formation and cell injury (van der Zee, 1987;Sminia et al, 1994).…”
Section: 1421mentioning
confidence: 99%
“…7.6 x 3.7 x 6.0 mm 18.0 x 7.9 x 9.7 mm 14.0 x 11.0 x 14.4 mm D294 7.9 x 5.9 x 6.4 mm 11.4 x 6.3 x 6.4 mm 23.0 x 10.0 x 15.8 mm Observed adverse effects during and following WBTT included hypotension, tachypnea, anorexia and skin lesions. In human medicine, it has been shown that while WBTT increases the heart rate, a drop in the systemic vascular resistance occurs during WBTT when the body temperature exceeds 40°C (Kerner et al, 2002), most likely due to alterations in thermal sensitivity of arterial baroreceptors and/or effects on the central nervous system (Haveman et al, 2004). The dopamine CRI in the dog of the present case successfully counteracted the hypotension.…”
Section: Discussionmentioning
confidence: 49%
“…WBH is accompanied by a markedly hyperdynamic cardiovascular state, which can result in a drop in arterial blood pressure that is chiefly due to a substantial decrease of the peripheral vascular resistance [27,[30][31][32]. In order to guarantee sufficient perfusion of vital organs, the mean arterial blood pressure should be maintained above 50 mmHg during the entire treatment.…”
Section: Induction Of Wbhmentioning
confidence: 98%